1998
DOI: 10.1007/s002590050221
|View full text |Cite
|
Sign up to set email alerts
|

Value of iodine-123 metaiodobenzylguanidine scintigraphy in patients with vasospastic angina

Abstract: To assess the presence and location of presynaptic myocardial sympathetic abnormality in patients with vasospastic angina, iodine-123 labelled metaiodobenzylguanidine (MIBG) single-photon emission tomography (SPET) was performed. Fifty patients suspected of having vasospastic angina pectoris were enrolled in the study. All patients underwent a provocative test with intracoronary ergonovine infusion during coronary angiography, in which 99%-100% obstructive spasm was defined as a positive result. Twenty-five pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…As a regional MIBG defect is also found in VA, some investigators believe that MIBG is useful for detecting VA, although its diagnostic value is controversial. [22][23][24][25] In contrast to regional MIBG defects, the H/M ratio and washout rate of MIBG are generally accepted as reflecting the global cardiac sympathetic nervous system. In heart failure, a reduced H/M ratio, which reflects enhanced cardiac sympathetic activity, is strongly associated with prognosis.…”
Section: Mibgmentioning
confidence: 99%
“…As a regional MIBG defect is also found in VA, some investigators believe that MIBG is useful for detecting VA, although its diagnostic value is controversial. [22][23][24][25] In contrast to regional MIBG defects, the H/M ratio and washout rate of MIBG are generally accepted as reflecting the global cardiac sympathetic nervous system. In heart failure, a reduced H/M ratio, which reflects enhanced cardiac sympathetic activity, is strongly associated with prognosis.…”
Section: Mibgmentioning
confidence: 99%
“…This antegrade flow before coronary intervention might protect the myocardium from irreversible damage but not be sufficient to protect sympathetic neuronal function, because the sympathetic nerve is more vulnerable to ischemic injury than myocytes. 23,24 This statistically insignificant difference between the 2 groups in antegrade flow might partially affect the present results. Finally, in the human study of 123 I-MIBG and 201 Tl scintigraphy, early images were analyzed, because the early 123 I-MIBG image reflects the neuronal function better than the delayed image 34 and the early image of stress 201 Tl scintigraphy reflects the risk area of myocardial ischemia better than the delayed, redistribution image.…”
Section: Study Limitationsmentioning
confidence: 60%
“…Reduced MIBG uptake is also found in patients with angina pectoris but without MI. [23][24][25] These observations suggest that the vulnerability of sympathetic nerves to ischemia may differ from that of myocytes. In addition to neural PC, brief ischemia before prolonged ischemia might reduce the infarct size and, therefore, may have affected the TDS for the 201 Tl and 123 I-MIBG images in the present human study.…”
Section: Effect Of Pc On Neural Functionmentioning
confidence: 94%
“…The testing results of MIBG-based examinations have been described for a variety of other heart diseases, including: primary arrhythmias [41][42][43], myocardial ischaemia with infarction [14][15][16][17] or without [44][45][46][47][48], in the assessment of the development of the innervation system after heart transplant [11,12,49], in the assessment of cardiotoxicity of anticancer chemotherapy [50][51][52]. There are also numerous reports showing that the I-123-MIBG imaging enables effective monitoring of the effects of conventional pharmacological therapies; images of MIBG uptake are improved after therapy with beta-blockers and often associated with reduced volume of the ventricles, better LVEF and reduced symptoms of heart failure; carvedilol has been most extensively researched in this respect (the recent randomised multi-centre double-blind placebo-controlled study was the French study described by showed that a damage of the myocardial adrenergic system can be responsible for the significant clinical improvement generally observed at an early stage after TMLR, however, in the light of reinnervation, it is not responsible for the improvement covering a period of several years [64][65][66][67].…”
Section: Clinical Applications Of I-123-mibg Myocardial Examinationsmentioning
confidence: 99%